In Vitro Assessment of Proximate and Phytochemical Quantifications of Some Edible Fruits - Augustine, Apiamu; Uduenevwo, Evuen Francis; Okoro, Igunbor Christian; Maryann, Ozemoya Onimoiveghie (Nigerian Journal of Pharmaceutical and Applied Science Research, 2015)
The present study was done to ascertain comparatively, the proximate and phytochemical compositions of some edible fruits; Citrullus lanatus (watermelon), Cucumis sativus (Cucumber), Ananas comosus (pineapple) and Annona muricata (soursop). Proximate and phytochemical analysis on wet weight basis among the four fruits were statistically significant (p<0.05). Proximate analysis revealed that watermelon had the highest total fat, crude fibre and moisture contents (0.24, 0.99 and 41.97%) respectively but least in total carbohydrate (45.26%) ; soursop exerted the highest ash, crude protein and total carbohydrate contents (0.39%, 13.34% and 74.66% ) but least in total fat and moisture contents; 0.10% and 10.97% respectively. Phytochemical analysis revealed comparatively that; soursop had highest concentrations of phytate, oxalate, tannin, phenol and alkaloids among other fruits, but pineapple, cucumber and watermelon had least levels of phytate, oxalate, phenol tannin and alkaloid respectively. In view of the appreciable levels of the nutrients and phytochemicals in the fruits, the results therefore suggest that regular consumption of these fruits would be safe for human health and effective management of some pathological conditions.